Republic of Belarus : Fourth Review Under the Stand; By Arrangement. (IMF Staff Country Reports; Country Report, 2010)
This paper discusses key findings of the Fourth Review Under the Stand-By Arrangement for Belarus. All end-December quantitative and continuous performance criteria and structural benchmarks were met. Discussions focused on confirming the authorities' commitment to program objectives, including with regard to lending under government programs, and on measures to reduce or offset the effects of higher prices on oil imports. The authorities also proposed to increase domestic prices of oil products and restructure the oil refining industry to reduce the need for subsidies.